DAMPAK PRAKTIK KOLABORASI INTERPROFESIONAL YANG EFEKTIF DALAM MENINGKATKAN HASIL PERAWATAN - Aliyah, Ira Nur; Putri Zaenal, Keysha Bilbina; Fernanda, Kenita Amelia; Rahmawati, Mira; Utami, Pamela Meiranda (Jurnal Keperawatan dan Kesehatan, 2025)
Interprofessional collaboration is increasingly vital in healthcare, yet it faces numerous challenges. These barriers can originate at the organizational level, such as unclear standard operating procedures, rigid hierarchies, an imbalance in the recognition of roles among healthcare professions, and systems that inadequately support teamwork. This study aims to evaluate the effectiveness of interprofessional collaboration in improving patient care outcomes. Employing the PICO framework and the Scoping review methodology, this study analyzed literature from the Scopus, PubMed, Science Direct, and SpringerLink databases, supplemented by the Google Scholar search engine, for publications from 2020–2024. From the 10 selected articles, the findings indicate that interprofessional collaboration effectively enhances communication within healthcare teams. Structured and coordinated collaboration facilitates more organized, significant, and comprehensive care, as every aspect of a patient's needs can be thoroughly addressed. This increases patient satisfaction and contributes to more optimal care outcomes. Therefore, interprofessional collaboration not only positively impacts healthcare team communication but is also capable of improving patient care outcomes.